Perancangan Ulang Tata Letak Fasilitas Internal Warehouse Untuk Meminimasi Ongkos Material Handling - Adinda Bela Patria; Muhammad Hisjam (Institut Transportasi dan Logistik Trisakti, 2021)
Warehouse of Company X has two production supply destinations, TFD 315 and TFD 500. One of the supply destinations has a high workload for the forklift driver. It happened because of the long distance when doing material handling. Warehouse’s layout of company X is not optimal that causing huge material handling costs. So, relayout of the facilities is done in order to reduce material handling costs by shortening the distance between facilities based on the relationship of material handling activities. The stages of this research are data collection, calculating distance and material handling costs for the initial facility layout, making the activity relationship chart (ARC) between facilities, planning the new facility layout, then calculating the distance and cost of material handling of the new layout, and the last is comparing the initial and the new material handling costs. The results of this research is that after doing relayout of warehouse facility layout, material handling costs are reduced by 21.07% from the initial cost.